A new variants of quasi-newton equation based on the quadratic function for unconstrained optimization - Basim Abbas Hassan; Mohammed W. Taha (Institute of Advanced Engineering and Science, 2020)
The focus for quasi-Newton methods is the quasi-Newton equation. A new quasi-Newton equation is derived for quadratic function. Then, based on this new quasi-Newton equation, a new quasi-Newton updating formulas are presented. Under appropriate conditions, it is shown that the proposed method is globally convergent. Finally, some numerical experiments are reported which verifies the effectiveness of the new method.